Efficacy and safety of 650 nm invasive laser acupuncture on non-specific chronic low back pain: a randomized clinical trial - Hong, Yejin; Nam, Dongwoo; Yang, Changsop; Kang, Byoung-Kab; Kim, Ae-Ran; Shin, Kyung Min; Kim, Jihye; Jeon, Saerom; Park, Gwang-Cheon; Kim, Jae-Hong (Frontiers in Medicine, 2025)
BackgroundThe study aims to determine whether 650 nm invasive laser acupuncture (ILA) is safe and effective for pain relief in patients with non-specific chronic low back pain (NSCLBP).MethodsThis randomized clinical trial was conducted in two hospitals in Korea. Individuals with NSCLBP were randomized into two groups: an ILA group and a control group, in a ratio of 1:1. One hundred six participants with NSCLBP were equally assigned to the 650 nm ILA group and the control group. The 650 nm ILA group underwent 650 nm ILA for 10 min, and the control group received sham ILA for 10 min per visit, twice a week for 4 weeks, bilaterally at the GB30, BL23, BL24, and BL25 acupuncture points. All participants were trained on exercise and self-management. The primary outcome was the responder rate at the 3-day post-treatment endpoint, defined as the proportion of patients with more than a 30% reduction in NSCLBP.ResultsAt the 3-day post-treatment endpoint, participants in the treatment group were approximately 36% more likely to respond to the treatment than those in the control group (odds ratio 4.69; 95% confidence interval, 2.04, 10.79; p < 0.001), indicating a statistically significant difference in responder rates between the two groups.ConclusionOur study provides clinical evidence for the safety and efficacy of 650 nm ILA in managing of NSCLBP. This is the first study to use ILA, which differs from previously used conventional laser acupuncture.Systematic review registrationhttps://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&focus=reset_12&search_page=M&pageSize=10&page=undefined&seq=21591&status=5&seq_group=21591, identifier registration KCT0007167.